Loss of genetic diversity and increased genetic structuring in response to forest area reduction in a ground dwelling insect: a case study of the flightless carabid beetle Carabus problematicus (Coleoptera, Carabidae). Issue 4 (6th November 2012) - Gaublomme, Eva; Maebe, Kevin; Van, Karine; Dhuyvetter, Hilde; Li, Xiang; Desender, Konjev; Hendrickx, Frederik; Boomsma, Jacobus
Abstract Old growth temperate broadleaved forests are characterised by a large proportion of forest specialists with low dispersal capability. Hence, species bound to this habitat are expected to be highly susceptible to the effects of decreasing patch size and increasing isolation. Here, we investigate the relative effect of both factors by genotyping individuals of a flightless and forest specialist beetle Carabus problematicus from 29 populations, sampled in 21 different forest fragments in Belgium, at eight microsatellite loci. A high degree of genetic differentiation among fragments was observed, with populations from smaller forests being considerably more differentiated and characterised by a lower genetic diversity compared to those of larger forests. A more detailed study on forest remnants of a former historic continuous woodland area revealed that population differentiation was high among, but not within remnants, irrespective of geographical distance. This suggests that patch fragmentation rather than geographical distance is the ultimate factor that hampers gene flow in this species. The results indicate that gene flow among suitable habitat patches is primarily reduced by the inability of this specialised species to traverse the landscape matrix. This lack of dispersal may pose a serious threat for the persistence of C. problematicus and ecologically similar species, and suggests that present populations can best be protected by securing or increasing the size of existing habitat patches.